(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
Today, students in higher education institutions of developed countries are taught using the latest techniques and technologies. Also, in order to develop the professional competence of future builders-engineers in the field of construction in our republic, it is becoming important to expand the opportunities for students to work with multimedia, graphic imagination, architectural graphic tasks-projects, design drawings of buildings and structures based on foreign languages. Education in foreign languages is an important factor in providing future builders-engineers with competitive staff, knowledge, skills and literacy in their specialty, and the justification of the demands placed on them is of great relevance.